Estimation of groundwater recharge in semiarid regions under variable land use and rainfall conditions: a case study of Rajasthan, India - Yadav, Basant; Parker, Alison; Sharma, Anupma; Sharma, Rakesh; Krishan, Gopal; Kumar, Suraj; Le Corre Pidou, Kristell; Campo Moreno, Pablo (Public Library of Science (PLoS), 2023)
In the semiarid regions of India, the annual rainfall is very low (~650 mm) and erratic; hence groundwater recharge is vital to support crops, especially in the winter season. For groundwater budgeting it is essential to consider how groundwater recharge is affected by both land-use and rainfall distribution. This study used a soil water balance approach, considering hydrological, meteorological, hydrogeological and crop information to understand the recharge process in semiarid regions. The approach was used at a sub-watershed scale where farmers grow rainfed and irrigated crops. Delayed recharge response on the water table was considered to estimate actual recharge, which closely matches the observed water levels in the field. The recharge estimated in rainfed agricultural lands, rainfed-irrigated agricultural lands, and barren lands was 29%, 17%, and 31% of the total inflow.